Psychological and cognitive factors implicated in pain experience in women with endometriosis. Issue 1 (4th March 2022) - Zarbo, Cristina; Brugnera, Agostino; Compare, Angelo; Malandrino, Chiara; Candeloro, Ilario; Secomandi, Rita; Betto, Enrico; Bellia, Adriano; Rabboni, Massimo; Bondi, Emi; Frigerio, Luigi
Abstract: Sixty women with a diagnosis of endometriosis (30 with low pain severity - LP; 30 with high pain severity - HP) were evaluated at study entry (T0) and after three months (T1). At T0 they were compared for different psychological dimensions to sixty-two age-paired healthy women (CG). HP group had significantly higher scores on depressive symptomatology, sexual distress, and catastrophizing than CG, and higher scores on worry traits than LP. Metacognitive beliefs predicted sexual distress at T1, over and above pain severity. Pain affects different domains of mental health in this population. Coping strategies, metacognitive beliefs, and worry traits may modulate pain experience and psychological distress.